Humanity at the heart of practice : a study of ethics for health-care students and practitioners - Whelton, Beverly J.; Neuenschwander, Jane (Cambridge Scholars Publishing, 2019)
Humans are the only beings in the world who are concerned with what ought to be done. They perceive the impact of another human's action as good or evil, moral or immoral. Healthcare is humans caring for other vulnerable humans and ethics evaluates the way humans treat each other, so follows logically that this book about ethical decision-making in healthcare uses humanity as its organizing structure. The book begins by considering values and good reasoning. Philosophy is concerned with what can be known through the power of human reason, so we need to consider what it is to know, to grasp con.